Alone on the ice [compact disc, unabridged] : the greatest survival story in the history of exploration - Roberts, David, 1943- (Blackstone Audio, Inc., 2013)
On January 17, 1913, alone and near starvation, Mawson, leader of the Australasian Antarctic Expedition, was hauling a sledge to get back to base camp. The dogs were gone. Now Mawson himself plunged through a snow bridge, dangling over an abyss by the sledge harness. A line of poetry gave him the will to haul himself back to the surface. On February 8, when he staggered back to base, his features unrecognizably skeletal, the first teammate to reach him blurted out, "Which one are you?" This thrilling and almost unbelievable account establishes Mawson in his rightful place as one of the greatest polar explorers and expedition leaders. Included is a trove of Frank Hurley's famous Antarctic photographs, many never before published in the United States.